the students' ability to identify the generic structure of recount text - Wiwik Yully Widyawati (Scope : Journal of English Language Teaching, 2019)
The purpose of the study is to find out the students ability in identifying the generic structure of recount text, the problems faced by the students and solution of the problems faced by the students in identifying the generic structure of recount text. This method used descriptive qualitative method. The writer used essay test, 10 items. The writer took sample randomly, thirty six students. The findings of this research are by analyzing the students’ test which are done by the students about of identifying the recount text . After the data have been collected and analyzed, the score of the students’ ability to identify the generic structure of recount text is 73.9. It means that the students’ ability in identifying the generic structure of recount text is fair. However, the problems that faced by the students in identifying the generic structure of recount text are the students found the difficulty in understanding the meaning of the word and question, and they can’t identify the generic structure of recount text completely especially the part of event. Then, to overcome the problems, the writer offers some suggestions. They are the teacher should give more exercises in analyzing the generic structure especially event, give more attentions to the result of the assignment which are given to the students.Key words: genre, generic structure, and recount text